Small organic molecules containing amorphous calcium phosphate: synthesis, characterization and transformation - Indurkar, Abhishek; Kudale, Pawan; Rjabovs, Vitālijs; Heinmaa, Ivo; Demir, Öznur; Kirejevs, Matvejs; Rubenis, Kristaps; Chaturbhuj, Ganesh; Turks, Māris; Locs, Janis (Frontiers in Bioengineering and Biotechnology, 2024)
As the primary solid phase, amorphous calcium phosphate (ACP) is a pivotal precursor in cellular biomineralization. The intrinsic interplay between ACP and Howard factor underscores the significance of understanding their association for advancing biomimetic ACP development. Amidst the well-established role of organic compounds in biomineralization, we present a synthesis of ACP with naturally occurring organic compounds (ascorbate, glutamate, and itaconate) ubiquitously present in mitochondria and crucial for bone remodeling and healing. The developed ACP with organic compounds was meticulously characterized using XRD, FTIR, and solid-state 13 C and 31 P NMR. The morphological analysis revealed the characteristic spherical morphology with particle size close to 20 nm of all synthesized ACP variants. Notably, the type of organic compound strongly influenced true density, specific surface area, particle size, and transformation. The in vitro analysis was performed with MC3T3-E1 cells, indicating the highest cell viability with ACP_ASC (ascorbate), followed by ACP_ITA (itaconate). The lowest cell viability was observed with 10 %w/v of ACP_GLU (glutamate); however, 1 %w/v of ACP_GLU was cytocompatible. Further, the effect of small organic molecules on the transformation of ACP to Ap was examined in Milli-Q® water, PBS, and α-MEM.